Case report: Watch-and-wait strategy in resectable esophageal cancer following neoadjuvant chemoimmunotherapy: a case series - Tan, Lingyu; Yang, Guozhen; Zeng, Chufeng; Zhang, Xu (Frontiers in Immunology, 2025)
Neoadjuvant chemoimmunotherapy (NCIT) has improved pathological complete response and conferred survival benefits in patients with locally advanced esophageal cancer. However, surgical complications unrelated to the tumor continue to detract from patient outcomes. While the “watch-and-wait” strategy has been implemented in clinical complete responders following neoadjuvant therapy for rectal cancer, there is a lack of evidence supporting its practicability in esophageal cancer after NCIT. This pilot case series involves six clinical complete responders who deferred surgery under close surveillance after three or four cycles of neoadjuvant camrelizumab plus chemotherapy and who subsequently received camrelizumab as maintenance treatment. The primary observation measure of the series is event-free survival (EFS). Routine follow-up examinations included endoscopy, biopsy, contrast-enhanced computed tomography, and ultrasonography every 3–6 months. For patients who experienced local recurrence without metastasis, the salvage operation was the priority recommendation. As of September 5, 2024, the average follow-up duration was 124.4 weeks, with the average EFS reaching 134.7 weeks. No deaths or distant metastases were observed. Our findings suggest that responders to NCIT may be spared from esophagectomy. On the prerequisite of sufficient tumor regression during neoadjuvant cycles, immunotherapy may facilitate the continued eradication of residual disease in this series.